Valence control of charge and orbital frustrated system YbFe2O4 with electrochemical Li+ intercalation. (March 2022) - Murase, S.; Yoshikawa, Y.; Fujiwara, K.; Fukada, Y.; Teranishi, T.; Kano, J.; Fujii, T.; Inada, Y.; Katayama, M.; Yoshii, K.; Tsuji, T.; Matsumura, D.; et al.
Abstract: We report an attempt valence control of the mixed valence iron triangular oxide YbFe2 O4 to develop an effective technique controling the frustration of charges in strongly correlated electron systems. The electrochemical doping of Li  +  into YbFe2 O4 was examined on a cell-type sample similar to the Li-ion secondary battery cell. Systematic changes in the lattice constant and Fe – Fe and Fe–Yb distance were observed with Li doping. Maximum value of the doping was over 300 mAh/g. An EXAFS experiment indicated that Li positioned between Yb octahedron layer (U-layer) and Fe-bipyramidal layer (W-layer). However, detailed change of iron valence state of YbFe2 O4 was not clearly observed because of the superimpose of the signal from iron metal nano particles in XANES observation. We discuss that the uncertainty might arise from the inhomogeneous distribution of the sample particle size, which might prevent the homogeneous doping of Li because the doping occurs on the surface of each nano-particles. Highlights: The electro-chemical doping of Li  +  into an electronic ferroelectric material YbFe2 O4 was examined for valence control of iron ions. Systematic change of the lattice constant, Fe–Fe and Fe–Yb distance were observed. Maximum of Li was over 300 mAh/g, but above 100 mA/g, the sample disassembled to iron nano particles. An EXAFS experiment indicated that Li may position between Yb layer and Fe layer.